2020
DOI: 10.1371/journal.pntd.0007888
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic landscapes increase Campylobacter jejuni infections in urbanizing banded mongoose (Mungos mungo): A one health approach

Abstract: Background Campylobacter is a common, but neglected foodborne-zoonotic pathogen, identified as a growing cause of foodborne disease worldwide. Wildlife and domestic animals are considered important reservoirs, but little is known about pathogen infection dynamics in free-ranging mammalian wildlife particularly in sub-Saharan Africa. In countries like Botswana, there is significant overlap between humans and wildlife, with the human population having one of the highest HIV infection rates in the world, increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Data from the articles reviewed showed that at least twelve Campylobacter species have been detected in wild animals in 36 countries and the Antarctica Peninsula [ 15 , 16 , 38 , 40 , 41 , 42 , 43 , 46 , 48 , 49 , 50 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 ...…”
Section: Wildlife Carriers Of Campylobacter Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from the articles reviewed showed that at least twelve Campylobacter species have been detected in wild animals in 36 countries and the Antarctica Peninsula [ 15 , 16 , 38 , 40 , 41 , 42 , 43 , 46 , 48 , 49 , 50 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 ...…”
Section: Wildlife Carriers Of Campylobacter Speciesmentioning
confidence: 99%
“…Rhynd et al [ 85 ] demonstrated that asian mongooses ( Herpestes javanicus ) are carriers and shedders of Salmonella and Campylobacter spp. Moreover, Medley et al [ 66 ] sampled fecal samples in humans, free-ranging banded mongooses ( Mungos mungo ) surface water, and river sediment samples in northern Botswana and reported Campylobacter spp. and C. jejuni as the main bacterium free-ranging banded mongooses ( M. mungo ).…”
Section: Wildlife Carriers Of Campylobacter Speciesmentioning
confidence: 99%